How physics flew the philosophers' nest. (August 2021) - Brading, Katherine; Stan, Marius
Abstract: We all know that, nowadays, physics and philosophy are housed in separate departments on university campuses. They are distinct disciplines with their own journals and conferences, and in general they are practiced by different people, using different tools and methods. We also know that this was not always the case: up until the early 17th century (at least), physics was a part of philosophy. So what happened? And what philosophical lessons should we take away? We argue that the split took place long after Newton's Principia (rather than before, as many standard accounts would have it), and offer a new account of the philosophical reasons that drove the separation. We argue that one particular problem, dating back to Descartes and persisting long into the 18th century, played a pivotal role. The failure to solve it, despite repeated efforts, precipitates a profound change in the relationship between physics and philosophy. The culprit is the problem of collisions. Innocuous though it may seem, this problem becomes the bellwether of deeper issues concerning the nature and properties of bodies in general. The failure to successfully address the problem led to a reconceptualization of the goals and subject-matter of physics, a change in the relationship between physics and mechanics, and a shift in who had authority over the most fundamental issues in physics.